2000
DOI: 10.1115/1.483269
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Circumferential Film Thickness Distribution in Horizontal Annular Gas-Liquid Flow

Abstract: This paper develops a liquid film symmetry correlation and a liquid [11m thickness distribution model for horizontal annular gas-liquid pipe flows. The symmetry correlation builds on the work of Williams et al. (1996). A new correlating parameter is presented. The experimental data used in the correlation is from all three of the horizontal annular flow regions: stratified-annular,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 11 publications
1
19
0
2
Order By: Relevance
“…compared with values given by the Hulburt and Newell[23] model (diameters in millimeters).D m/0=0.95 (G=50kg/m 2 s) Downloaded by [National Sun Yat-Sen University] at 16:46 27 December 2014…”
mentioning
confidence: 99%
“…compared with values given by the Hulburt and Newell[23] model (diameters in millimeters).D m/0=0.95 (G=50kg/m 2 s) Downloaded by [National Sun Yat-Sen University] at 16:46 27 December 2014…”
mentioning
confidence: 99%
“…This model for the liquid film has been implemented by several researchers, including Owen and Hewitt [25] and Hurlburt and Newell [26], with some success. Dobran has shown that a model modifying this profile by reducing the turbulent mixing somewhat as the gas-liquid interface is approached gives much better agreement to physical behavior [27,28].…”
Section: Thin Film Particle Image Velocimentry In Annular Flowmentioning
confidence: 99%
“…The Wallis [4] correlation, as well as the correlations of Hurlburt and Newell [6], which proceed from the work of Asali et al [5], use film thickness to calculate interfacial shear. The correlation labeled Hurlburt and Newell (1) uses this dimensionless film thickness as part of a linear term, while that labeled Hurlburt and Newell (2) uses it in an exponential term.…”
Section: Correlationsmentioning
confidence: 99%
“…Among film thickness correlations, one of the earliest was that of Wallis [4], who proposed a friction factor scaling in an offset linear fashion with film thickness. More complex correlations have evolved, including those of Asali et al [5] and Hurlburt and Newell [6]. Some have used the proposed interrelationship to derive complete two-fluid models, such as those of Owen and Hewitt [7] and Hurlburt et al [8].…”
Section: Introductionmentioning
confidence: 98%